THE EFFECT OF WORKPLACE SPIRITUALITY ON AUDIT QUALITY WITH JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT AS A MEDIATION VARIABLE - Muhamad Fuji Hakiki; Yayu Putri Senjani (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
This study aims to analyze the effect of workplace spirituality on audit quality with job satisfaction and organizational commitment as mediation. The sampling technique used purposive sampling using non-experimental primary data (questionnaire). This study uses a multivariate analysis tool with 2 methods, namely the first generation technique and the second generation technique. The results showed that (1) workplace spirituality had a positive and significant effect on audit quality through job satisfaction, (2) workplace spirituality had a positive and significant effect on audit quality through organizational commitment not proven